The power of information: The ICT revolution in agricultural development - Nakasone, Eduardo; Torero, Máximo; Minten, Bart (Annual Reviews, 2014)
We review the state of information and communication technologies (ICTs) and their impact on agricultural development in developing countries, documenting the rapid changes that have taken place over the past decade. Although there remains a wide gap in access between rural and urban areas, the spread of mobile phones in rural areas has led to important changes in the agricultural sector. We find that access to mobile phones has generally improved agricultural market performance at the macro level; however, impacts at the micro level are mixed. Evidence regarding the impact of market information systems (MIS) delivered through mobile phones on farm prices and income is limited, but the evidence points to strong, heterogeneous impacts. Similarly, the rollout of extension programs though ICTs is still in an early stage, and little research is available regarding such programs’ impacts.